THE NORMATIVE AND LEGAL FOUNDATIONS OF REFORMS IN THE EDUCATION SYSTEM OF UZBEKISTAN - D. Karimova (Galaxy International Interdisciplinary Research Journal, 2022)
The progress of any society and the expected result of its future tasks depend first of all on a generation with a broad outlook and personnel with modern thinking, deep knowledge and potential. In this perspective, the role of the educational process is incomparable. For this reason, in the last five years, reforms related to the education and training process in our country have accelerated. In this way, special attention was paid to each stage of education. In particular, the coverage of pre-school education was increased to 67%, and more than 500 general secondary schools were newly established. The number of more than 70 higher education institutions in use has been increased from 140.